PEMBERDAYAAN KADER AISYIYAH DALAM PROMOSI PIJAT BAYI DI NGAMPILAN YOGYAKARTA - Rahmah Rahmah; Erfin Firmawati; Nurul Hidayah (LPPM IST AKPRIND Yogyakarta, 2020)
Baby massage is a tradition of decline in the family and society of Indonesia, because baby massage is believed to have many benefits for the baby as a stimulus for baby's growth and development and through family massage can communicate and as a form of attention, affection and acceptance among fellow family members brotherhood relationships besides love and affection among family members can be obtained by strengthening attachment bonding through baby massage classes intended for families and babies. Baby massage does not always have to be done in “ dukun pijat bayi”, clinics or other health services because mothers can do baby massage at home. The right way to massage a baby can be learned with training, so that all mothers who have babies can have the opportunity to learn the right way to massage babies needed by some human resources who are willing to train mothers to do baby massage at home while promoting baby massage in the community. The purpose of this activity was to empower “ kader Aisyiyah”promoting baby massage in community.